The Effect of Nurturing Program, Boarding School, and The Use of Social Media on The Character Building of Politeknik Ilmu Pelayaran Semarang Cadets - Andy Wahyu Hermanto; Ariyanti Sri Nugraheni; Dhadhang Tri Sudarmoyo; Achmad Ridwan (Research Synergy Foundation, 2024)
Character building is very essential for cadets. As future leaders and officers on commercial ships, they are expected to have strong personalities, be disciplined, be responsible, have high integrity, and be able to work together in a team. Based on this issue, this research aims to analyze the effect of nurturing programs, boarding schools, and social media on the character-building of Politeknik Ilmu Pelayaran (PIP) Semarang cadets. This research used a quantitative method with respondents PIP Semarang cadets from the Nautical Studies, Marine Engineering, and Port and Shipping Management Study Program with a sample of 200 cadets. Sampling was conducted using a questionnaire via Google Form with a Likert scale of 1 to 4. Data obtained from the questionnaire were analyzed using the SPSS 21st version program. The results of this research show that the nurturing program has a very significant influence on the character-building of cadets. Thus, if the nurturing program can be implemented well and correctly according to established norms and regulations, the character of the cadets will be built well and meet the expectations of PIP Semarang. In addition, the boarding school system has a significant influence on the character-building of cadets. A well-built Boarding School system will assist in shaping the characters of PIP Semarang cadets. Lastly, the use of social media does not significantly influence cadets' character-building since there is a regulation related to the limitation of the use of communication devices and the internet.